Museu e escola : espaços de sentidos - Mattos, Ivana de Macedo (2015)
This research aims to understand how the Art Museum of Espírito Santo (MAES) acts in the production of meaning for the students, from the relations stablished with the school, and, in this proceeding, how the museum understands art and school as a final goal to its actions. The research subjects were 98 5th grade children of a private Elementary School in Vitória. The research had as corpus the verbal-visual discourses produced by the children in this link between museum and school, as well as discourse performances from the Educational Programme of Action of the Museum, regarding the teacher training and the lecture circle program. The research methodology used the exploratory study and the theoretical framework was semiotics discursive semiotics. The data collection took place in the museum and in the school. In the Museum, from events that guided the exhibition " My Tropical country," from the german artist Heidi Lieberman , and from educational activities proposed by MAES; in the school, with the initial mapping to understand how and what directions were pointed out by the children concerning their knowledge about art and about an art museum (that happened before their first visit to this space , what they know and what understanding they have of art), as well as in their visual and verbal- visual productions after their visit to the museum institution. Finally, for analysing the verb-visual texts, there were dialogues with the stages of cognitive development proposed by Michael Parsons (2002). The survey results indicate that the analytical methodology of discursive semiotics contributed significantly to uncover the directions indicated by the children in the museum and in the school. Through the verbal-visual discourses produced by them, it was understood that an education for the sensitive, aligned with good meetings in the museum and in the school, may have power and provide a unique and significant experience that sharpens the sensitivity and brings back the enchantment in education.